Evidences for Different Reaction Sites for Dehydrogenation and Dehydration of Ethanol over Vanadia Supported on Titania - Kim, Yu Kwon; Ryu, Seol (Bulletin of the Korean Chemical Society, 2019)
Vanadia supported on titania were prepared with increasing vanadia loadings up to 20 wt % to study the effect of the vanadia loading on catalytic reactivity. A competitive decomposition of ethanol into ethylene (dehydration) and acetaldehyde (dehydrogenation) over the catalyst occurs over the vanadia supported on TiO2. Dehydrogenation is generally favored over dehydration over a wide range of the vanadia loadings up to 20 wt % due to a lower energy barrier for the dehydrogenation channel. Both dehydration and dehydrogenation rates are enhanced in proportion to the vanadia loadings up to about 2 wt %. At higher vanadia loadings (>2 wt %), however, the dehydration rate decreases while the dehydrogenation rate saturates. X-ray photoelectron spectroscopic analysis reveals that reduced V and Ti species are formed at the low vanadia contents and act as strong dissociative adsorption sites for H2O, while extended VOx clusters as well as three-dimensional V2O5 islands formed at high vanadia loadings prevent the formation of such sites. Thus, the observed difference between the two reaction channels can be explained from the structural transition of the vanadia overlayers from highly dispersed small VOx clusters into larger polyvanadates or islands. At low vanadia loadings (<2 wt %), both the edge sites and the surface sites of the small VOx clusters grow in proportion to the loadings as the number of the clusters increases. Thus, both reaction channels are enhanced as well. At higher vanadia loadings (>2 wt %), however, the transformation into larger islands reduces the edge sites or the boundaries between the clusters and TiO, not the surface area. This implies that the active sites for the dehydrogenation are on the surfaces of the vanadia overlayers, while those for the dehydration are on the boundaries between the VOx and TiO2. Our results provide an additional insight into the active sites for dehydration and dehydrogenation reactions over the titania-supported vanadia catalysts.
Keywords: Catalytic reactivity; Dehydration of ethanol; Dehydrogenation reactions; Dissociative adsorption; Lower energy barriers; Structural transitions; Vanadia; X-ray photoelectrons; Dehydration; Dehydrogenation; Ethanol; Vanadia/TiO2